THE EFFECT OF ERGONOMIC GYMNASTICS ON CHANGES OF BLOOD SUGAR LEVELS IN ELDERLY WITH DIABETES MELITUS - LEXY OKTORA WILDA; FITRA HANDIKA HUTAMA; DATI KUNTARI (NURSING ANALYSIS: Journal of Nursing Research, 2022)
ABSTRACT Ergonomic gymnastics can prevent and treat various diseases, because the muscles are moved optimally, so that more absorbs blood sugar for the burning process and sugar levels will decrease towards normal. The purpose of this study was to determine the effect of ergonomic gymnastics on changes in blood sugar levels in the elderly with diabetes mellitus. The design of this study was pre-experimental with the Pre-Post Test Design approach. The study population was all elderly who were diagnosed with DM, as many as 35 people. Samples were taken by total sampling technique to obtain a sample size of 35 respondent. The independent variable was ergonomic gymnastics and the dependent variable was the change in elderly blood sugar levels. Data collection instruments used were GCU easytouch blood sugar levels and observation sheets. Data was analyzed by Paired Sample T-Test with α = 0.05. The results showed that the blood sugar levels of the elderly before being given ergonomic gymnastics therapy, almost half were equal to 251-300 mg / dl as many as 16 as many as the elderly (45.7%). Elderly blood sugar levels before being given ergonomic gymnastics therapy, most of which was 201-250 mg / dl as as many as 18 elderly (51.4%). It was evidenced from the results of the Paired Sample T-Test indicating that p-value = 0,000 ≤ α (0.05) so Ha was accepted, meaning that there is an effect of ergonomic gymnastics on changes in blood sugar levels in the elderly with diabetes. Ergonomic gymnastics therapy for 2 weeks in this study has succeeded in reducing blood sugar levels in the elderly with DM in Prolanis Pace Bugar Berseri. Significant reduction in blood sugar levels has been proven through statistical tests, but it is still temporary and must be maintained through a healthy lifestyle. Keywords: Blood Sugar Levels, Elderly with Diabetes Mellitus, Ergonomic Gymnastics SENAM ERGONOMIS TERHADAP PERUBAHAN KADAR GULA DARAH PADA LANSIA DENGAN DIABETES MELITUS ABSTRAKSenam ergonomis dapat mencegah dan mengobati penyakit diabetes melitus, karena otot-otot digerakkan secara optimal, sehingga lebih banyak menyerap gula darah untuk proses pembakaran dan kadar gula akan menurun menuju normal. Tujuan penelitian mengetahui pengaruh senam ergonomis terhadap perubahan kadar gula darah pada lansia dengan diabetes mellitus. Desain penelitian ini adalah pre eksperimen dengan pendekatan Pre-Post Test Design.  Populasi adalah seluruh lansia terdiagnosa DM, yaitu sebanyak 35 orang. Sampel diambil dengan teknik total sampling sehingga diperoleh besar sampel sebanyak 35 lansia. Variabel independen adalah senam ergonomis dan variabel dependen adalah perubahan kadar gula darah lansia. Instrumen kadar gula darah easytouch GCU dan lembar observasi. Analisa data menggunakan uji Paired Sample T-Test dengan α = 0.05. Hasil penelitian menunjukkan bahwa kadar gula darah lansia sebelum diberi terapi senam ergonomis, hampir setengahnya adalah sebesar 51-300 mg/dl, yaitu sebanyak yaitu sebanyak 16 lansia (45,7%). Kadar gula darah lansia sesudah diberi terapi senam ergonomis, sebagian besar adalah sebesar 201-250 mg/dl, yaitu sebanyak yaitu sebanyak 18 lansia (51,4%). Hal ini dibuktikan dari hasil uji Paired Sample T-Test menunjukkan bahwa p-value = 0,000 ≤ α = 0,05 sehingga Ha diterima. Terapi senam ergonomis selama 2 minggu dalam penelitian ini telah berhasil menurunkan kadar gula darah pada lansia dengan DM. Penurunan kadar gula darah tersebut secara signifikan telah dibuktikan melalui uji statistik, namun sifatnya masih sementara dan harus terus dipertahankan melalui pola hidup yang sehat.Kata Kunci: Senam Ergonomis, Kadar Gula Darah, Lansia DM